2023
DOI: 10.3390/polym15040911
|View full text |Cite
|
Sign up to set email alerts
|

Fourier Transform Infrared Spectroscopy to Assess the Degree of Alteration of Artificially Aged and Environmentally Weathered Microplastics

Abstract: Fourier transform infrared (FTIR) is a spectroscopy technique widely used to identify organic materials. It has recently gained popularity in microplastic (MP) pollution research to determine the chemical composition of unknown plastic fragments. However, it could also be used to evaluate the degree of ageing of MPs collected from the environment. In this context, the principal aim of our research has been to qualitatively evaluate the natural weathering of environmental MPs collected in an Italian freshwater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 56 publications
(83 reference statements)
2
26
0
Order By: Relevance
“…The carbonyl index can reect the aging degree of materials to a certain extent. 37,38 Combining the changes in carbonyl index and gloss loss rate of PEG2000 samples during the three UV irradiations for 600 h (Fig. 11), it can be found that there is a good correlation between the two, especially in the 351 and 313 nm UV irradiation.…”
Section: Discussion Of Photoaging Behavior and Mechanismmentioning
confidence: 94%
“…The carbonyl index can reect the aging degree of materials to a certain extent. 37,38 Combining the changes in carbonyl index and gloss loss rate of PEG2000 samples during the three UV irradiations for 600 h (Fig. 11), it can be found that there is a good correlation between the two, especially in the 351 and 313 nm UV irradiation.…”
Section: Discussion Of Photoaging Behavior and Mechanismmentioning
confidence: 94%
“…The reference peak is the absorption peak uninfluenced by photoaging. 34 In this study, we used the carbonyl stretching vibration peak at 1723 cm −1 and the methyl stretching vibration peak at 1453 cm −1 as the maximum carbonyl absorption peak and the reference peak, respectively. These peaks were used to calculate the carbonyl index (CI) relative to the CH 3 group.…”
Section: Resultsmentioning
confidence: 99%
“…Fourier Transform Infrared (FTIR) spectroscopy was used to elucidate the functional groups found in the materials [10]. Attenuated Total Reflectance (ATR) was the method used for FTIR analysis in this research.…”
Section: Sample Preparation and Microplastic Identificationmentioning
confidence: 99%